Pengembangan Virtual Tour Fakultas Teknik Universitas Negeri Yogyakarta Menggunakan Foto 360 Derajat - Annasbiq Ahsanal Haq; Eko Marpanaji; Adi Dewanto (Department of Electronics and Informatics Engineering Education, 2023)
The research on the development of Virtual Tour at the Faculty of Engineering of Yogyakarta State University using 360 degree photos has purpose to develop a virtual tour using 360 degree photos as a media tour of the Faculty of Engineering of Yogyakarta State University, describe the performance of the virtual tour, and describe the feasibility of the virtual tour. This research uses a research and development (R&D) type with a V-Model development model. The V-Model has stages of Requirement Analysis & Acceptance Testing, Specification & System Testing, Architecture Design & Integration Testing, Implementation & Unit Testing. The subjects in this study are students of the Faculty of Engineering of Yogyakarta State University and the general public, with a total of 36 respondents. The research instrument used to determine the feasibility of the virtual tour consists of black box testing, assessment sheets for media experts, and research sheets for respondents. The results of the study showed that the development produced a virtual tour media of the Faculty of Engineering of Yogyakarta State University using 360 photos. The result of media expert validation obtained a percentage of 83.59% and falls into the